Structural features of iron vacuum condensates alloyed with tungsten - Barmin, A.E.; Zubkov, A.I.; Il'inskii, A.I. (Functional Materials, 2012)
Initial structure and composition of Fe-W vacuum deposited films were studied using the methods of transmission electron microscopy, X-ray diffraction, energy-dispersive spectroscopy, and X-ray fluorescence analysis. It was shown that tungsten microalloying resulted in the grain dispersion of iron matrix. The tungsten non-homogeneous distribution within each grain has been revealed. The features observed are explained by the alloying component grain-boundary segregations formed under condensation of two-component vapor.